Primeiro registro de crypticerya zeteki (Cockerell, 1914) (Monophlebidae) no Brasil e maconellicoccus hirsutus (Green, 1908) (Pseudococcidae) no Maranhão, Brasil - Ramos, A. S.J.C.; Peronti, A. L.B.G. [UNESP]; Kondo, T.; Lemos, R. N.S. (FapUNIFESP (SciELO), 2018)
Crypticerya zeteki (Cockerell, 1914) (Hemiptera: Coccomorpha: Monophlebidae) is recorded for the first time from Brazil and Maconellicoccus hirsutus (Green, 1908) (Hemiptera: Coccomorpha: Pseudococcidae) is recorded for the first time from the state of Maranhão, Brazil. Both species were collected from branches, leaves and fruits of various fruit trees in the municipalities of São José de Ribamar, São Luís and Paço do Lumiar, Maranhão, Brazil. Crypticerya zeteki was collected on Citrus spp. (Rutaceae), Cocos nucifera (L.) (Arecaceae), Cycas revoluta L. (Cycadaceae), Malpighia punicifolia L. (Malpighiaceae), Mangifera indica L. (Anacardiaceae), Musa paradisiaca L. (Musaceae) and Theobroma grandiflorum Schum (Malvaceae), all first records for this species. Maconellicoccus hirsutus was collected on Spondias tuberosa Arruda (Anacardiaceae) and M. punicifolia L. (Malpighiaceae), both new records for this species.
First record of crypticerya zeteki (Cockerell, 1914) (Monophlebidae) in Brazil and maconellicoccus hirsutus (Green, 1908) (Pseudococcidae) in the state of Maranhão
Keywords: Biodiversity; Geographical distribution; Mealybug; Neotropical region